Doping in sport a defence - Petersen, Thomas S. (Thomas Søbirk) (Routledge focus on sport, culture and society, 2021)
In this provocative and thought-provoking book, Professor of Ethics Thomas Sbirk Petersen explains why the World Anti-Doping Agency's doping rules are poorly justified and makes a case for a new third way in anti-doping policy that would allow athletes to use substances and methods currently on WADA's prohibited list. The book identifies, clarifies and challenges the central arguments that are used in the often highly emotional debates around doping, and argues strongly that open dialogue about doping is essential as it defines the territory in which athletes, physicians, managers, coaches and pharmaceutical companies can operate safely. It is rooted in the theory of ethics and illustrated with real cases, examples and experiences from sport at all levels, from the auto-biographical to some of the most high-profile doping cases in history. This is an essential addition to the bookshelves of researchers and students of sports studies like sports philosophy, sports law, sports medicine and the sociology of sport, and a fascinating read for anybody interested in the darker side of sport and in its possible futures.